PENJUALAN PONSEL PINTAR TANPA GARANSI RESMI DI TENGGARONG BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Andi Setiawan (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTSince Law Number 8 of 1999 concerning Consumer Protection has been enacted and along with the development of technology, the use of technolopgy products, especially telematics and electronic products in Indonesia, has experienced rapid development from year to year. Warranty is a full stage transaction from the stages of consumer transactions. Considering the importance of the after-sales guarantee / guarantee card and to complete the UUPK, the Minister of Trade Regulation of the Republic of Indonesia Number 19 / M-DAG / PER / 5/2009 was issued. With this regulation, it is expected that consumers can avoid purchasing defective or damaged products. The author in conducting this research uses the method of empirical juridical research, namely research carried out by collecting data directly from competent parties in connection with the object under study, for this method of interviewing with staff and agencies is related to the object of this research to obtain primary data. aims to find out the legal consequences for businesses that trade smart phones without an official guarantee in Tenggarong city and find out the settlement efforts for consumers who have been harmed by buying smart phones without an official guarantee under Law Number 8 of 1999 concerning Consumer Protection.KEY WORDS:Due to Law, Consumer Protection, UUPK